Giant Thrombosis at Left Anterior Descending Artery Aneurysm in a 10-Year Old Boy with Granulomatosis with Polyangiitis. (22nd April 2020) - Aghaei Moghadam, Ehsan; Aslani, Nahid; Mojtabavi, Helia; Larti, Farnoosh; Ghamari, Azin; Ziaee, Vahid
Abstract : Granulomatosis with polyangiitis (GPA), necrotizing vasculitis of small and medium-sized vessels, is traditionally believed to mainly affect respiratory tract with additional focal kidney involvements as its primary manifestations with a relatively rare annual incidence rate of 20-50 cases per million. Six percent of the affected cases have cardiac involvements; among which, aneurysms comprise the lowest penetrance. By this paper, we aim to cast light on clinical diagnostic and treatment methods of a rare case presentation, a 10-year-old male GPA patient, diagnosed with massive thrombosis at his coronary artery aneurysm. GPA should be considered as differential diagnosis of prolong fever and coronary aneurysms in adolescents.